2013
DOI: 10.3171/2012.10.spine12321
|View full text |Cite
|
Sign up to set email alerts
|

Use of prone position magnetic resonance imaging for detecting the terminal filum in patients with occult tethered cord syndrome

Abstract: The authors' new method of using the prone position for MRI shows that the terminal filum is located significantly posterior and the cauda equina is located anterior in patients with OTCS, suggesting a difference in elasticity between the terminal filum and cauda equina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
(31 reference statements)
0
15
0
2
Order By: Relevance
“…Performing MRI in different body positions has been evaluated to facilitate diagnosing occult TCS in people. Decreased spinal cord motion between the prone and supine position has been considered suggestive for TCS 15, 17. The dog presented here, recovered completely after surgical transection of the filum terminale.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…Performing MRI in different body positions has been evaluated to facilitate diagnosing occult TCS in people. Decreased spinal cord motion between the prone and supine position has been considered suggestive for TCS 15, 17. The dog presented here, recovered completely after surgical transection of the filum terminale.…”
mentioning
confidence: 56%
“…A proportion of people with primary TCS present with the conus medullaris in a normal position. This is referred to as occult TCS 15, 16. Considering these arguments, it cannot be excluded the dog described here presented with occult TCS instead of TCS with an abnormal caudodorsal position of the conus medullaris.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…18 With improved imaging (e.g., MRI and significantly improved noninvasive imaging methods) neurosurgeons can now more readily diagnose TCS based on clinical and radiographic findings. 3,8,33 MRI and ultrastructural light and electron microscopy studies have shown that decreased elastic properties of the filum may exist in patients with TCS. 13,33 Technological advancements within the past few decades have allowed prenatal diagnosis of spina bifida and prenatal repair of myelomeningocele to become possible.…”
mentioning
confidence: 99%
“…3,8,33 MRI and ultrastructural light and electron microscopy studies have shown that decreased elastic properties of the filum may exist in patients with TCS. 13,33 Technological advancements within the past few decades have allowed prenatal diagnosis of spina bifida and prenatal repair of myelomeningocele to become possible. 2 Although there has been progressive insight into the various causes of TCS within the past century, with clinical and pathological properties becoming better understood, there is a lack of Class I data about surgical outcomes with resulting controversy and disagreement.…”
mentioning
confidence: 99%